Extramural venous invasion (EMVI) revisited: a detailed analysis of various characteristics of EMVI and their role as a predictive imaging biomarker in the neoadjuvant treatment response in rectal cancer - Altinmakas, Emre; Dogan, Hakan; Taskin, Orhun Cig; Ozoran, Emre; Bugra, Dursun; Adsay, Volkan; Balik, Emre; Gurses, Bengi (Abdominal imaging, 2022)
Purpose To assess whether size, diameter, and large vein involvement of MR-detected extramural venous invasion (MR-EMVI) have an impact on neoadjuvant therapy response in rectal adenocarcinoma. Methods 57 patients with locally advanced rectal adenocarcinoma scanned with MRI before and after neoadjuvant therapy were included. Two abdominal radiologists evaluated the images with special emphasis on EMVI, on initial staging and after neoadjuvant treatment. The sensitivity and specificity of MRI for detection of rest EMVI were determined. The association of various MR-EMVI characteristics including number, size, and main vein involvement with treatment response was investigated. In subjects with discordance of radiology and pathology, elastin stain was performed, and images and slides were re-evaluated on site with a multidisciplinary approach. Results At initial evaluation, 17 patients were MR-EMVI negative (29.8%) and 40 were MR-EMVI positive (70.2%). Complete/near-complete responders had less number (mean 1.45) and smaller diameter of MR-EMVI (mean 1.8 mm), when compared with partial responders (2.54 and 3.3 mm; p < 0.005). The sensitivity of MRI for rest EMVI detection was high, specificity was moderate, and in one patient elastin stain changed the final decision. In five patients with rest MR-EMVI positivity, carcinoma histopathologically had a distinctive serpiginous perivascular spread, growing along the track of vascular bundle, although it did not appear in intravascular spaces. Conclusion This study demonstrates that not only the presence, but also size and number of EMVI that may be significant clinically and thus these parameters also ought to be incorporated to the MRI evaluation and prognostication of treatment response. From pathology perspective, tumors growing alongside major vessels may also reflect EMVI even if they are not demonstrably “intravascular.” Graphical abstract